Nesprin-2G tension fine-tunes Wnt/β-catenin signaling - Gottardi, Cara J. (J Cell Biol, 2020)
How LINC complexes mediate nuclear mechanotransduction remains unclear. In this issue, Déjardin, Carollo, et al. (2020. J. Cell Biol. https://doi.org/10.1083/jcb.201908036) show that the LINC complex protein nesprin-2G is a mechanosensor of epithelial–mesenchymal transitions (EMTs), recruiting α-catenin to the nucleus to attenuate Wnt/β-catenin signaling.